Cardiopulmonary resuscitation : the short comings in Malaysia. - Sheng, Chew Keng; Zakaria, Mohd Idzwan; Rahman, Nik Hisamuddin Nik Abdul; Jaalam, Kamaruddin; Adnan, Wan Aasim Wan (2008)
This short review explores the current status of cardiopulmonary resuscitation in Malaysia and highlights some of the factors that have a negative impact on its rate of success. Absence of a unifying body such as a national resuscitation council results in non-uniformity in the practice and teaching of cardiopulmonary resuscitation. In the out-of-hospital setting, there is the lack of basic skills and knowledge in performing bystander cardiopulmonary resuscitation as well as using an automated external defibrillator among the Malaysian public. The ambulance response time is also a significant negative factor. In the in-hospital setting, often times, resuscitation is first attended by junior doctors or nurses lacking in the skill and experience needed. Resuscitation trolleys were often inadequately equipped.